Portraits of underprivileged Filipino second language learners: Towards the development of computer-based educational game - Bringula, Rex (Archīum Ateneo, 2018)
This study determined the portraits of underprivileged language learners in attempt to design educational software for them. Toward this goal, we conducted an ethnographic study which involved surveys and interviews of the informants (i.e., teachers). Textual analysis on the responses of the informants revealed that underprivileged language learners can be classified into four types. Implications to computer-based educational game design are also offered.